2015
DOI: 10.1007/s12291-015-0533-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Contraceptive Pills on the Blood Serum Enzymes and DNA Damage in Lymphocytes Among Users

Abstract: The continuous use of synthetic hormones as contraceptive pill or hormonal replacement therapy among women is increasing day by day. The widespread use of different formulations as oral contraceptives by women throughout their reproductive cycle has given rise to a serious concern for studying the effects of oral contraceptives on enzymatic profile and DNA damage in peripheral blood lymphocytes among users. The present study was carried out on women taking oral contraceptives. The study was based on the questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
1
6
1
Order By: Relevance
“…Current findings are in correlation with the previous studies where an increase in the plasma levels of AST and ALT has been reported 55,56 . However, the results are contrary to the studies that indicate a decrease in the ALP level 55 However, the mainly two members are Firmicutes and Bacteroidetes 58 . The study found 12 different bacterial phyla in our samples among all groups.…”
Section: Discussionsupporting
confidence: 93%
“…Current findings are in correlation with the previous studies where an increase in the plasma levels of AST and ALT has been reported 55,56 . However, the results are contrary to the studies that indicate a decrease in the ALP level 55 However, the mainly two members are Firmicutes and Bacteroidetes 58 . The study found 12 different bacterial phyla in our samples among all groups.…”
Section: Discussionsupporting
confidence: 93%
“…In a recent study by Falaq Naz et al showed hormonal contraceptives seem to exert DNA damage and also have significant effects on blood serum enzymes [15]. Very few authors in the literature have observed these types of chromosomal aberrations, also they were unable to give statistical analysis of these types as observed in present study.…”
Section: Resultscontrasting
confidence: 60%
“…Types, numbers, total changes and mutagenic index (%) obtained for the negative (CO-) and positive (CO+) control groups and the groups treated with different female contraceptives, at times 0, 24 and 48 hours. In a search conducted by Naz et al (2016), for assessing DNA damage to blood lymphocytes, the authors indicated that the longer the period of use of oral contraceptives, the greater the damage found. This hypothesis can be verified according to the reports of Ahmad et al (2001), who confirmed the genotoxic potential of synthetic progestins, used as contraceptives, and the influence of time and dose in the experiments was also observed.…”
Section: Resultsmentioning
confidence: 99%